KADAR 2,3-DINOR-6-KETO-PROSTAGLANDIN-F1 DALAM URIN WANITA PASCAMENOPAUSE ALAMI DAN PRAMENOPAUSE YANG MINUM ASPIRIN 100 MG - Arieselia, Zita; Setiawati, Arini; Setiabudy, Rianto; Baziad, Ali (Bahasa Indonesia, 2011)
Background: The prevalence of cardiovascular diseases in women increases sharply after menopause. In postmenopausal women, thromboxane production increases while prostacyclin production decreases. Low dose aspirin (75- 150 mg) has long been known as an antiplatelet aggregator. Aspirin reduces the production of both thromboxane (potent thrombocyte aggregator and vasoconstrictor) and prostacyclin (anti thrombocyte aggregator and potent vasodilator).Methods: The present study was an open-label clinical trial with 2 parallel groups. One group consisted of 15 premenopausal women (age > 40 years) while the other group 15 postmenopausal women (for 3 - 5 years). Twenty-four hours urine was collected from each subject before and after aspirin 100 mg daily for 7 days. The concentration of prostacyclin was measured as its metabolite (2,3-dinor-6-keto-prostaglandin-F1) in urine using EIA (Enzyme Immunoassay). Thromboxane as its urinary metabolites (11-dehidrotromboksan-B2) was also measured in these same urine samples in the previous study.Results: Previous study showed that aspirin significantly reduced thromboxane in both groups, with significantly larger percentage reduction in postmenopausal women compared to premenopausal women. Results of the present study showed that aspirin reduced prostacyclin significantly in both premenopausal women (mean difference = 78.44 ng/g creatinine; p = 0.001) and postmenopausal women (mean difference = 35.71 ng/g creatinine; p <0.001), but the percentage reduction between the groups was not significantly different (46,26% vs. 40,94%; p = 0,574). The decrease in thromboxane and prostacyclin should be compared (as the decrease in the ratio of 11-dehidrotromboksan-B2 / 2,3-dinor-6-keto-prostaglandin-F1) to assess aspirin efficacy as an antithrombotic. Calculation of the ratio of 11-dehidro-tromboksanB2 / 2,3-dinor-6-keto-prostaglandin-F1 before aspirin consumption was much higher in postmenopausal women compared to that in premenopausal women (4.09 vs. 1.13; p = 0.001). The decrease in 11-dehidro-tromboksan-B2 / 2,3- dinor-6-keto-prostaglandin-F1? ratio by aspirin was found much larger in postmenopausal women compared to that in premenopausal women (1.91 vs.0.17; p = 0.022).Conclusions: It was concluded that aspirin reduced prostacyclin significantly in each group with nonsignificant percentage reduction between groups, but reduced the 11-dehidro-tromboksan-B2/2,3-dinor-6-keto-prostaglandin-F1? ratio much larger in post-menopausal women compared to that in premenopausal women.